Genotyping respiratory viruses in sudden unexpected death in infancy cases (SUDI) at Tygerberg Medico-legal Mortuary - Vanmali, Hameer Deepak (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.